Finite element analysis of patient-specific additive-manufactured implants - Namvar, Arman; Lozanovski, Bill; Downing, David; Williamson, Tom; Kastrati, Endri; Shidid, Darpan; Hill, David; Buehner, Ulrich; Ryan, Stewart; Choong, Peter F.; Sanaei, Reza; Leary, Martin; et al. (Frontiers in Bioengineering and Biotechnology, 2024)
Introduction: Bone tumors, characterized by diverse locations and shapes, often necessitate surgical excision followed by custom implant placement to facilitate targeted bone reconstruction. Leveraging additive manufacturing, patient-specific implants can be precisely tailored with complex geometries and desired stiffness, enhancing their suitability for bone ingrowth. Methods: In this work, a finite element model is employed to assess patient-specific lattice implants in femur bones. Our model is validated using experimental data obtained from an animal study (n = 9). Results: The results demonstrate the accuracy of the proposed finite element model in predicting the implant mechanical behavior. The model was used to investigate the influence of reducing the elastic modulus of a solid Ti6Al4V implant by tenfold, revealing that such a reduction had no significant impact on bone behavior under maximum compression and torsion loading. This finding suggests a potential avenue for reducing the endoprosthesis modulus without compromising bone integrity. Discussion: Our research suggests that employing fully lattice implants not only facilitates bone ingrowth but also has the potential to reduce overall implant stiffness. This reduction is crucial in preventing significant bone remodeling associated with stress shielding, a challenge often associated with the high stiffness of fully solid implants. The study highlights the mechanical benefits of utilizing lattice structures in implant design for enhanced patient outcomes.